Outcome of the Treatment of Distal Tibia Fractures by Minimal Invasive Locked Plate – A Short Term Study - Jha, Ranjib Kumar; Gupta, Yogendra; Karn, Navin (Journal of Nobel Medical College, 2017)
Background :Treatment of fracture distal tibia is challenging. Classic open reduction and internal plate fixation requires extensive soft tissue dissection and causes periosteal injury. The locking screw-plate interface allows fracture fixation without plate–bone adherence, thus preserving the fracture hematoma, and reduces the risk of nonunion by maintaining microvascular circulation within the cortex and its investing tissues. Material & Methods: This study included 33 patients of age between 18 to 62 years with extra-articular and simple intra-articular fracture of distal tibia. All fractures were fixed by minimally invasive technique with pre-countered distal tibia locking plate under image intensifier control. The American Orthopaedic Foot and Ankle Society (AOFAS) scale was used for functional assessment. Results: Out of 33 there were twelve 43-A1, five A2, five A3, five B1, three B2, two C, one C2 fractures. There were 29 closed fracture and four open fracture (three type I and one type II). The overall mean time of union was 16.3 weeks. The mean AOFAS score was 93 points. In all 30 cases there were no wound problems, whereas three cases had superficial wound infection. No any cases needed secondary procedure for healing of bone. Conclusion: The short-term results shows that minimally invasive locked plating is good solution for the challenging distal tibia fracture. This technique minimizes soft tissue complication and provides good union and functional outcome. Journal of Nobel Medical College Volume 6, Number 1, Issue 10 (January-June, 2017), page: 12-19